"Measures of Dissipation in Viscoelastic Media" Extended: Toward Continuous Characterization Across Very Broad Geophysical Time Scales. Issue 16 (27th August 2019) - Lau, Harriet C. P.; Holtzman, Benjamin K.
Abstract: We develop a conceptual/quantitative framework whereby measurements of Earth's viscoelasticity may be assessed across the broad range of geophysical processes, spanning seismic wave propagation, postseismic relaxation, glacial isostatic adjustment, and mantle convection. Doing so requires overcoming three challenges: (A) separating spatial variations from intrinsic frequency dependence in mechanical properties; (B) reconciling different conceptual and constitutive viscoelastic models used to interpret observations at different frequencies; and (C) improving understanding of linear and nonlinear transient deformation mechanisms and their extrapolation from laboratory to earth conditions. We focus on (B), first demonstrating how different mechanical models lead to incompatible viscosity estimates from observations. We propose the determination of the "complex viscosity"—a frequency‐dependent parameter complementary to other measures of dissipation (including frequency‐dependent moduli and attenuation)—from such observations to reveal a single underlying broadband mechanical model. The complex viscosity illuminates transient creep in the vicinity of the Maxwell time, where most ambiguity lies. Key Points: Inferences of viscous dissipation across frequencies from earthquakes to convection yield very different estimates of viscosity Discrepancies can be explained by spatial variations and/or frequency‐dependent mechanical properties We propose a framework for inferring transient creep in signals across broad geophysical time scales